Local Wisdom and Financial Accountability in Traditional Village Governance: An Institutional Theory Approach - Kadek Supri Budiadnyana; Putu Sukma Kurniawan; I Putu Gede Diatmika (LifeSciFi, 2026)
Growing demands for accountability and transparency in public financial management have driven institutions to adapt formal governance systems while preserving local cultural values. This study examines financial management in Alapsari Traditional Village through the lens of institutional theory, focusing on the integration of Sad Kerthi values within formal governance systems. It aims to explore the implementation of Sad Kerthi values in financial management practices. A qualitative case study approach was employed, using in-depth interviews, observations, and NVivo-based thematic analysis. The findings show that financial management operates within a hybrid institutional model, where regulative, normative, and cultural-cognitive pillars interact dynamically. Sad Kerthi values are not merely symbolic but are operationalized across planning, implementation, and accountability processes through participatory mechanisms such as paruman, resulting in holistic accountability that encompasses administrative, social, and spiritual dimensions, supported by strong social control and high integrity in financial practices. The study concludes that integrating local wisdom with formal governance enhances transparency, legitimacy, and sustainability, although challenges related to human resource capacity and regulatory adaptation persist. These findings contribute to the development of culturally grounded public sector accounting and provide practical insights for improving financial governance in traditional communities.